2009
DOI: 10.1246/cl.2009.96
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Procedure for Acetalization of Aldehydes and Ketones Catalyzed by Cerium(III) Trifluoromethanesulfonate

Abstract: Aldehydes and ketones are readily protected in the presence of trialkyl orthoformate and a catalytic amount of cerium(III) trifluoromethanesulfonate under mild conditions to give the corresponding acetals in good to excellent yields. Due to the mild reaction conditions, this method is compatible with acid-sensitive substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…2 Because of the versatility and usefulness of acetals in organic synthesis, several methods for the protection [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the selective, mild deprotection 21 of aldehydes and ketones have been described. The classical procedure for protection involves the Lewis [3][4][5][6][7][8][9][10][11][12][13][14][15] or protic acid-catalyzed [16][17][18][19][20] reaction of a carbonyl compound with a large excess of an alcohol in the presence of a water scavenger. Among the employed Lewis acids are metal triflates, [3][4][5][6][7][8] 19 and silica-supported HClO 4 20 have been used as protic acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Because of the versatility and usefulness of acetals in organic synthesis, several methods for the protection [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the selective, mild deprotection 21 of aldehydes and ketones have been described. The classical procedure for protection involves the Lewis [3][4][5][6][7][8][9][10][11][12][13][14][15] or protic acid-catalyzed [16][17][18][19][20] reaction of a carbonyl compound with a large excess of an alcohol in the presence of a water scavenger. Among the employed Lewis acids are metal triflates, [3][4][5][6][7][8] 19 and silica-supported HClO 4 20 have been used as protic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The classical procedure for protection involves the Lewis [3][4][5][6][7][8][9][10][11][12][13][14][15] or protic acid-catalyzed [16][17][18][19][20] reaction of a carbonyl compound with a large excess of an alcohol in the presence of a water scavenger. Among the employed Lewis acids are metal triflates, [3][4][5][6][7][8] 19 and silica-supported HClO 4 20 have been used as protic acids. Despite the advocated advantages of several recently described methods for the acetalization reaction, they have some drawbacks, such as the use of toxic, strong and corrosive acids, non-recyclable catalysts, volatile organic solvents (VOCs) and, in some cases, non-commercially available catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these molecules are water-compatible catalysts, an important property for reactions such as acetalization/ketalization, which generate water as a byproduct (Scheme ). Indeed, Sc­(OTf) 3 , Ce­(OTf) 3 , and Yb­(OTf) 3 are known to catalyze acetalizations/ketalizations under mild conditions. We recently found that Lu­(OTf) 3 is an efficient catalyst for acetone ketalization with glycerol .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, green catalysis has been found to be the method of choice for the production of acetals. For instance, researchers have used many catalysts for the acetalization of carbonyl compounds such as, lanthanum(III)nitrate hexahydrate (Srinivasulu et al, 2008), bismuth subnitrate (Wu et al, 2008), anhydrous CeCl 3 (Silveira et al, 2010), cerium(III) trifluoromethanesulfonate (Ono et al, 2009) tetrafluoroboric acid adsorbed on silica gel (Kumar et al, 2008) and phosphotungstic acid and its cesium salt supported on dealuminated ultra-stable Y zeolites (Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%